Formalin detection device in Tofu food with telegram monitoring - Prayogo, Rio; Anshory , Izza; Sulistiyowati, Indah; syahrorini, Syamsudduha (Journal of Computer Networks, Architecture and High Performance Computing, 2023)
Tofu is a side dish or food used by many people. As a processed food product made from soybeans, white tofu contains protein and high water content so it is very good for the growth of spoilage microorganisms. As a result, tofu is not durable and easily damaged. Damage to white tofu is characterized by a sour and slimy odor. The usual preservation methods for traders include soaking tofu in formalin to make tofu more resistant to decay, resistant to microorganisms, and maintaining its freshness for up to seven days. Formalin to prevent unwanted things. In food Because of the above problems, there needs to be special treatment against excessive use of formalin in food in Indonesia. Formalin should be limited within International Chemical Safety Programme (IPCS) limits for adult foods containing formaldehyde. And also sensors made of polymeric materials combined with activated carbon to detect formalin in food. The development of technology continues with the development of internet products from things that can communicate with each other through the internet. Then a tool was developed to solve the above problem. As part of the research, a formaldehyde detection device will be made in tofu food with a monitoring telegram. The system uses HCHO sensors and a Node MCUESP 32 microcontroller, which is then transmitted through a database that allows you to view through the LCD screen and the Telegram Android smartphone application, of which of course many applications are installed to facilitate this. Users are able to check formalin plates remotely via an internet network connection.